Female adolescent athletes` awareness of the connection between menstrual status and bone health - Feldmann, J. M.; Belsha, J. P.; Eissa, M. A.; Middleman, A. B. (Journal of Pediatric and Adolescent Gynecology, 2011)
Study Objective: The aims of this study are to determine among female high school track athletes: (1) knowledge of the association between menstrual irregularity and bone health; (2) attitudes toward amenorrhea, specifically if amenorrhea is seen as a sign of athletic success; (3) the association between knowledge and attitudes based on athlete menstrual status. Design: Cross-sectional survey. Setting: Five public high schools in Texas. Participants: 103 female high school track athletes ages 14-18 years. Intervention: Participants completed a questionnaire that addressed menstrual history, details of track participation, knowledge of bone mineral density (BMD)/ menstrual status connection, and attitudes about the desirability of oligo/amenorrhea. Outcome Measures: Frequencies of attitude and knowledge replies, summative knowledge score, and correlations between attitudes, knowledge, and menstrual status. Results: Sixteen subjects (16.7%) met criteria for amenorrhea, 16 for oligomenorrhea (16.7%). Median summative knowledge score was one of six. Menstrual irregularity was associated with lower knowledge (P = 0.035). Incorrect answers about consequences of bone loss and the link to menstrual irregularity were given by =90% of respondents. Lower knowledge was associated with a greater number of "don`t know" replies to attitude questions (P = 0.002). Among more knowledgeable participants endorsing opinions, menstrual irregularity was not seen as a sign of athletic success. Conclusions: The prevalence of irregular menses is high among adolescent track athletes and a larger-scale inquiry to clarify adolescent athletes` knowledge of and attitudes about the link between menstrual patterns and BMD is indicated. Education may provide one key to improved health behavior among this at-risk population.